Theoretical Perspectives Of Occupational Health Nurses (OHN) Career In Indonesia: A Critical Review And Future Exploration - Hardy, Syaifoel; Tukayo, Isak JH; Afzal, Ridha; Hadi, Noor (Jurnal Berita Ilmu Keperawatan, 2021)
In practice the Occupational Health Nurses (OHN) in Indonesia do not have sufficient career objectives regardless of the availability of 30.381 medium-large industries. These opportunities and challenges prove that from the OHN employment viewpoint, the prospects for the OHN professionals are very promising. In terms of education where OH nursing specialization in Indonesia is still very limited, the career of the OHN corporate nursing profession needs to be analyzed and explored. This review aims to enhance the understanding of OH nurses' careers based on theoretical perspectives in an increasingly dynamic educational environment, provides comprehensive understanding of the work for OHN nurses and offers future research direction. The method used was Assessment Model of Meleis to review selected documents by implementing three types of career path, i.e. Career Framework, Change Model and Nursing Career Framework. There were 71 documents were reviewed include of the nursing education system by the Ministry of Health, the National Education System, Ministry of Higher Education (Ristekdikti), Development and Empowerment of Healthcare Human Resources (BPPSDM), AAOHN, OHN Career Guide Canada and several journals of the last five years, from 2016 to 2020. Meleis’ Model provides a deeper understanding of the OHN career. Meanwhile, reviewing career framework theories also contribute to the career path of OH Nurses, both in practice, research, education and administration in various dimensions of nursing care in the industrial settings.